Bladder cancer: detection and image quality compared among iShim, RESOLVE, and ss-EPI diffusion-weighted MR imaging with high b value at 3.0 T MRI. Issue 50 (December 2017) - Li, Hongyi; Liu, Lin; Shi, Qinglei; Stemmer, Alto; Zeng, Hong; Li, Yi; Zhang, Mengchao
Abstract : Abstract: To compare the detection of bladder neoplasms and image quality among the diffusion-weighted imaging (DWI) acquired by the prototype single-shot echo-planar-imaging (ss-EPI) sequence for integrated slice-specific dynamic shimming (iShim), readout segmentation of long variable echo trains (RESOLVE) and conventional ss-EPI sequences. Around 63 patients with 77 bladder lesions were enrolled. The MR protocol included T1WI, T2WI and 3 types of DWI. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of each DWI for the detection of bladder tumor were computed. The subjective scores of imaging quality, diagnostic confidence, and detection of tumors of stage T2 or greater were recorded. The contrast-to-noise ratio (CNR), signal intensity ratios, and apparent diffusion coefficient (ADC) values were measured. The univariate analysis of variance technique, the Friedman test, and Bland–Altman plots were used in the statistical analysis. Observer performance of tumor T stage was tested using receiver operating characteristic (ROC) curve analysis. The sensitivity, NPV, and accuracy of iShim (92.75%; 61.54%; 93.51%) for detection of bladder tumor were superior to those of RESOLVE (84.06%; 42.11%; 85.71%) and ss-EPI (86.96%; 47.06%; 88.31%). All qualitative scores of iShim were higher than RESOLVE (all P  < .05) and ss-EPI (all P  < .05). The CNR, signal intensity ratios between bladder lesion and urine, lesion, and submucosal stalk (or nearby normal bladder wall), and between distal normal bladder wall and urine of iShim (39.84 ± 12.11, 2.40 ± 0.60, 1.98 ± 0.43, 1.28 ± 0.16) were higher than RESOLVE (16.97 ± 7.08, 1.62 ± 0.41, 1.52 ± 0.42, 1.15 ± 0.29, all P  < .05) and ss-EPI (27.89 ± 9.65, 1.66 ± 0.46, 1.57 ± 0.50, 0.99 ± 0.22, all P  < .05). No significant difference of ADC values were found for iShim and RESOLVE ( P =0.46), iShim, and ss-EPI ( P  = 0.97), RESOLVE and ss-EPI ( P  = .48). The A z value for the detection of tumors of stage T2 or greater was slightly higher with the iShim DWI sequence (0.89) than with the RESOLVE (0.87, P  = 0.72) or ss-EPI (0.85, P  = .38) sequence. The iShim DWI has relatively better detection of bladder tumor and image quality without significant ADC value difference.